Cython a guide for Python programmers - Smith, Kurt W. (O'Reilly Media, 2015)
In this practical guide, you'll learn how to use Cython to improve Python's performance - up to 3000x - and to wrap C and C++ libraries in Python with ease. Author Kurt Smith takes you through Cython's capabilities, with sample code and in-depth practice exercises.